2015
DOI: 10.2486/indhealth.2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Association of active and passive smoking with occupational injury in manual workers: a cross-sectional study of the 2011 Korean working conditions survey

Abstract: This study was conducted to investigate the relationship of active and passive smoking with occupational injury among manual workers. Data from the 2011 Korean Working Conditions Survey were analyzed for 12,507 manual workers aged ≥15 yr. Overall, 60.4% of men and 5.8% of women were current smokers. The prevalence of injury was higher among never smokers who were exposed to secondhand smoke (SHS) (7.7% in men and 8.1% in women) than current smokers (4.2% in men and 4.1% in women). After controlling for potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A manual worker was defined as someone involved in an occupation that requires the handling of heavy or average loads on a regular basis, or occupations that involve handling lighter loads, but in static postures. In particular, an occupation variable that included agriculture, forestry, and fishery workers; craft and related trades workers; plant and machine operators and assemblers; cleaners and helpers; and unskilled labor were categorized as manual workers 21. These workers were regarded as a high-risk group for work-related stress and health outcomes 22.…”
Section: Discussionmentioning
confidence: 99%
“…A manual worker was defined as someone involved in an occupation that requires the handling of heavy or average loads on a regular basis, or occupations that involve handling lighter loads, but in static postures. In particular, an occupation variable that included agriculture, forestry, and fishery workers; craft and related trades workers; plant and machine operators and assemblers; cleaners and helpers; and unskilled labor were categorized as manual workers 21. These workers were regarded as a high-risk group for work-related stress and health outcomes 22.…”
Section: Discussionmentioning
confidence: 99%
“…The final sample size in the third KWCS was 50,032 native employees [ 12 ]. The cooperation rate of 66.2%, contact rate of 56.6%, refusal rate of 18.0% and response rate of 35.4% were calculated by the definition of the American Association for Public Opinion Research [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to a previous study, risk factors for occupational injury include personal factors such as age [ 20 ], hypertension or diabetes mellitus [ 21 22 ], smoking [ 23 ], and alcohol [ 24 25 ], and workplace factors such as workplace size [ 26 27 ], shift work [ 2 19 ], and type of industry [ 28 29 ]. In this study, when these factors were identified, men were found to have higher risk of occupational injuries in group of current smoking, drinking more than 15 units per week, working in workplaces with less than 300 workers, and non-shift work.…”
Section: Discussionmentioning
confidence: 99%